Gestiones de la (a)sexualidad infantil: una lectura del campo de investigaciones de las ciencias sociales en el ámbito latinoamericano = Childhood’s (a)sexuality managements: an approach to the research field in social sciences in Latin America - Anastasía González, Pilar (Civitas - Revista de Ciências Sociais)
Child (a)sexuality has been located in complex and diverse discourses through history. Currently there is an extended consensus of governmental apparatuses that recognize a large, comprehensive and positive definition for adult sexuality – for example the WHO`s definition of sexuality. However, when child sexuality is referred to, it is reduced to prevention restricting at the same time the conceptualization to a dangerous kind of sexuality. This operation, detected in a variety of social discourses corresponds to international right enunciations and also to the state of the art of social investigations towards childhood. The main objective of this article is to explicit some meanings of the age-sexual stratification, specifying some procedures of social discourse that construct and (re)produce it, particularly in the field of social investigations about sexual and reproductive rights